Temperature Effect on Lime Powder-Added Geopolymer Concrete - Sandeep L. Hake; R. M. Damgir; S. V. Patankar (Advances in Civil Engineering)
The need for concrete increases with rapid development in the field of infrastructure because of the increased use of cementing material of concrete. The production of concrete is unsafe to the earth. Consequently, there is a need to discover new binding material with cementing properties. Fly ash debris is wastage of thermal power plants and acquires hectares of land for the dumping reason. This paper concentrates on development of alternative binding material in the field of construction. The fly ash-based geopolymer concrete is a better option, but it needs heat curing for the polymerization. The use of lime powder in the geopolymer concrete gives better result without heat curing. The experiment depends on the characteristics of daylight curing and impact of temperature in controlled oven curing. The M30 grade geopolymer concrete plans with the addition of lime powder. The addition of lime powder is changed by 0%, 5%, 10%, 15%, 20%, and 25%. The compressive strength increases with addition of lime powder, but in the cases of 20% and 25%, the workability gets hamper. The study also deals with temperature variations when oven cured for 35°C, 40°C, 50°C, and 60°C hence assessed.